Mole balances on solid oxide fuel cells using natural gas as a fuel - Keith, Jason M. (Knovel, 2012)
Natural gas has been suggested as a possible intermediate fuel for a transition to a hydrogen economy. It is a plentiful resource in the United States, can easily be converted into hydrogen gas, and is already part of a current distribution infrastructure. One possible fuel cell that would be suited for large-scale electrical and thermal power generation is a solid oxide fuel cell (SOFC).
Keywords: Solid oxide fuel cells.; Gas as fuel.; elektronické knihy; electronic books